Analysis of electromyographic signals. - García Moreira, Carlos (Revista Mexicana de Ingenieria Biomedica, 1991)
In this article, the basic concepts of analogue to digital sampling of a physiological signal have been presented, as well as the representation of the information contained in said physiological signal, as well as the representation of the information contained in said signal over a space suitable to be more easily visualized and/or interpretable than the original signal. Therefore, in this presentation preference will be given to the operational aspects of those for the specific case of the electromyogram, emphasizing a phenomenological presentation, which will result in a more familiar concept for those who come from any of the medical-biological disciplines.